A Position Statement on Population Data Science: The Science of Data about People. (2018) - McGrail, Kim; Jones, Kerina; Akbari, Ashley; Bennett, Tell; Boyd, Andrew; Carinci, Fabrizio; Cui, Xinjie; Denaxas, Spiros; Dougall, Nadine; Ford, David; Kirby, Russell S; Kum, Hye-Chung; et al.
No abstract available